Somatic hypermethylation of MSH2 is a frequent event in lynch syndrome colorectal cancers - Nagasaka, Takeshi; Rhees, Jennifer; Kloor, Matthias; Gebert, Johannes; Naomoto, Yoshio; Boland, C. Richard; Goel, Ajay (Cancer research, 2010)
Heritable germline epimutations in MSH2 have been reported in a few Lynch syndrome families that lacked germline mutations in the MSH2 gene. It is not known whether somatic MSH2 methylation occurs in MSH2 mutation-positive Lynch syndrome subjects or sporadic colorectal cancers (CRC). Therefore, we determined the methylation status of the MSH2 gene in 268 CRC tissues, including 222 sporadic CRCs and 46 Lynch syndrome tumors that did not express MSH2. We also looked for microsatellite instability (MSI), germline mutations in the MSH2 and EpCAM genes, somatic mutations in BRAF and KRAS, and the CpG island methylator phenotype (CIMP). We observed that somatic MSH2 hypermethylation was present in 24% (11 of 46) of MSH2-deficient (presumed Lynch syndrome) tumors, whereas no evidence for MSH2 methylation existed in sporadic CRCs (MSI and microsatellite stable) or normal colonic tissues. Seven of 11 (63%) patients with MSH2 methylation harbored simultaneous pathogenic germline mutations in the MSH2 gene. Germline EpCAM deletions were present in three of four patients with MSH2 methylation but without pathogenic MSH2 germline mutations. The mean methylation scores at CIMP-related markers were significantly higher in Lynch syndrome tumors with MSH2 methylation than MSH2-unmethylated CRCs. In conclusion, our data provide evidence for frequent MSH2 hypermethylation in Lynch syndrome tumors with MSH2 deficiency. MSH2 methylation in this subset of individuals is somatic and may serve as the “second hit” at the wild-type allele. High levels of aberrant methylation at CIMP-related markers in MSH2-methylated tumors raise the possibility that MSH2 is a target susceptible to aberrant methylation in Lynch syndrome. Cancer Res; 70(8); 3098-108. ©2010 AACR.
Gesehen am 03.05.2023